(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2021)
The goal of current research to know the effectiveness of interactive teaching strategies and harmony Smithereens in the acquisition of scientific concepts and development of thinking Sounding teachers prepare students for the Institute. Find community was selected from fifth grade / branch of science and mathematics students in teacher / Karkh Morning Institute, two experimental groups , The first experimental group taught by Interactive teaching strategy and the second experimental group taught by Familiarize yourself Smithereens strategy, some of the variables that affect the experience of it had been checked and featured that two samples equal in these variables. Search has been prepared following tools: (Test the acquisition of scientific concepts; test amounted to paragraphs (60) paragraph of the type of multi-test, test thinking Sounding; test amounted to paragraphs (25) paragraph, After the application of tests and processing the results statistically revealed that there is a statistically significant difference in the acquisition of scientific concepts and thinking Sounding variable in favor of the first experimental group (interactive teaching strategy) in average test scores posttest and in the light of the results of the search it was reached a set of conclusions and recommendations.